The influence of responsible leadership on organizational commitment: the mediating role of trust in leaders in the higher education sector - Afzal, Muhammad; Soroya, Saira; Chaudhary, Naveed; Niazi, Abdul; Ashiq, Murtaza (RADS Journal of Business Management, 2025)
Background: This study examines the impact of responsible leadership (RL) on organizational commitment by examining the mediating role of trust in the leader, as modeled by the four key dimensions of the leader's role (aggregate of virtues, principles and ethical values, stakeholder involvement, and model of the leader's role) in the context of social identity theory. Methods: We employed a quantitative research design, surveying 300 middle-level employees in grades 11 to 16 from the University of the Punjab, Lahore, Pakistan. Data collection involved a structured questionnaire covering key leadership and trust dimensions. The data analysis utilized SPSS version 22 and ADANCO version 2.2, with structural equation modeling to test hypotheses. Results: Results show that organizational commitment is significantly influenced by stakeholder involvement (0.03 p-value) and ethical principles (0.00 p-value). The aggregate of virtues (0.79 p-value) and leadership role modeling (0.26 p-value) have an insignificant direct impact. However, trust significantly mediates the relationship between organizational commitment and stakeholder involvement (0.01 p-value). Trust’s mediation effect on the link between ethical principles and organizational commitment is minimal (0.04 p-value). Conclusion: This study suggests that implementing RL practices, particularly in stakeholder involvement and ethical leadership, enhances employee commitment. Responsible leadership cultivates a positive corporate image, attracting committed stakeholders. To maximize benefits, organizations should provide senior leaders with behavioral training in RL practices, fostering an environment that boosts employee loyalty. Leadership development programs should include modules on ethical decision-making, stakeholder communication, and trust-building strategies.
Keywords: Context (archaeology); Ethical leadership; Mediation; Organizational commitment; Stakeholder; Stakeholder engagement; Stakeholder theory; Structural equation modeling; dept.ils